Design of a Robot End-Effector Grabbing Mechanism Based on a Bionic Snake Mouth. (22nd March 2013) - Zhuang, Fu; Hangfei, Zhou; Zijuan, Liu; Jian, Fei; Weixin, Yan; Yanzheng, Zhao
Inspired by the bite and swallowing function of a snake's mouth, a robot end-effector grabbing mechanism was designed. The grabbing movement is realized by the 'bite' function of the bionic snake mouth actuator, and the 'swallowing' function insures a continuous grip on the object. To implement the continuous grip function of the new robot end-effector, the complex motion of a snake's mouth is simplified into three basic movements based on the anatomy of a snake's mouth and with a combination of bionics and engineering. The upper jaw consists of a double four-bar linkage mechanism and the lower jaw mechanism implementing a lateral expansion function are the two elements of the robot end-effector. The relationship model and the corresponding curves of the actuating force and gripping force are necessary to implement an open-loop control of the robot end-effector. Through analysis and simulation, linkage parameters are determined to implement the desired motion.